PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, PELATIHAN, LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS KEHUTANAN KABUPATEN KUTAI TIMUR - Suprapto . (Jurnal Paradigma (JP), 2017)
The purpose of this research is to describe and analyze the influence of leadership, motivation, training, and work environment on  employee’s performance in Forestry Department of East Kutai. The result of analysis shows that leadership variable, have a positive and significant influence to employees performance of Forestry Department of East Kutai. Work Motivation Variable, training and work environment according to analysis result are not significant, and don’t have any influence to employees performance of Forestry Department of East Kutai. Source of data taken from employees (Sample) of Secretariat, Utilization and Management of Forests Division, Production and Circulation of Forest Products Division, Rehabilitation and Forest Protection Division, Development and Forest Evaluation.